Le spectre de Thuit - Guerín, José Luis; Pladevall, Tomàs; Andrieu, Jessica; Auche, Anne Céline; Gautier, Juliette (José Luis Guerín, 2011)
Ostensibly framed as a restoration of a degraded found film recovered some 70 years after the sudden and unexplained death of its creator, a Parisian attorney and amateur filmmaker named Gérard Fleury at a lake in the village of Le Thuit in Normandy, "Tren de sombras" (Train of Shadows) is a dense, sensual, and richly textured exposition of José Luis Guerín's recurring preoccupations: the nature and subjectivity of the image-gaze, the permeable borders between truth and fiction, the role of architecture (and landscape) as palimpsest of hidden histories. By placing the discovery of Fleury's last shot footage of his home and family within the context of the ambiguity surrounding the circumstances of his death after a seemingly innocuous scouting trip early one morning to find suitable lighting conditions to incorporate into his home movie, the found film becomes both a curious artifact of the early days of cinema in its informally staged performances that suggest the whimsical, created illusions of Georges Méliès (in a performance of dancing ties and magic tricks), and also a non-fiction, historical record that can be deconstructed, reconstituted, and re-analyzed to glean further information into the real-life mystery. [filmref.com]